What Tourists Want, a Sustainable Paradise - Cathrine Linnes; Jerome Agrusa; Giulio Ronzoni; Joseph Lema (Tourism and Hospitality, 2022)
The increasing complexity of tourism and sustainability offers opportunities and challenges among diverse stakeholder perspectives. The need for sustainable and nature-based approaches exists throughout the growing body of literature from among a number of dimensions and measures. One of the overarching goals of the paper is to examine whether tourists will choose a destination or hotel that is actively working to improve the environment while examining how Hawaii’s tourism is nature-based as well as other measures of sustainability while enjoying a slice of paradise in the Hawaiian Islands. This study explores tourism sustainability concerns in Hawaii, such as the influence of the tourist sector on the environment and will address if Hawaii should be recognized as a sustainable tourism destination. A survey instrument was developed where 454 respondents participated. According to the findings of this research, tourists visiting Hawaii support environmentally sustainable tourism practices leading towards a more sustainable tourist destination.